Effect of Storage Time for Broiler Chicken Meat at a Temperature of 40 c with the Provision of Kaffir Lime Leaf Oil (Citrus Hystrix Dc) - Netty Maria Naibaho; Asri Santalina Naibaho; Rudito (Formosa Journal of Applied Sciences, 2023)
The storage process is an important factor in maintaining the shelf life of raw boiler chicken meat. The aim of the research was to determine the use of kaffir lime leaf essential oil on the shelf life of raw boiler chicken meat wrapped in overwrapping at a cold temperature of 4oC. 2.5 mL of kaffir lime leaf essential oil with a concentration of 1.5% was sprayed onto Whatman No.1 filter paper. Samples were taken on days 0, 1, 3, 5, and 7 at a storage temperature of 4oC. The total value of salmonella sp. and the overall total viable count (TVC) was calculated, and sensory type analysis was performed to determine the panelist's level of preference. The results show that the shelf life of raw boiler chicken meat is approximately 5 days. Kaffir lime leaf essential oil can extend the shelf life of boiler chicken meat for about 2 days.